The first report of ants (Formicidae: Hymenoptera) in salt marshes and salt pans in central parts of Iran - MOHAMMAD REZA MOHSENI; SHAHROKH PASHAEI RAD (Society for Indonesian Biodiversity, 2019)
The present study was conducted in Salt marshes and Salt pans in central parts of Iran. 121 specimens of ants were collected by trapping and hand during spring, summer and autumn 2017 to 2019. Nine species belong to two subfamilies of Myrmicinae and Formicinae were identified. The vegetation, physical and chemical parameters of soil such as salinity, Ph, and other factors were investigated. Darband Shoor Mountain station with five species had the highest diversity and vegetation density and the lowest salinity of soil (72.14 ds/m) whereas Salt Lake station had only one species, with no vegetation and the highest salinity of soil (153.15 ds/m). Cataglyphis lividus (André, 1881) was the dominant species in all the stations except in Darband Shoor Mountain station. All the species were reported for the first time from salt marshes and salt pans in the central parts of Iran and were approved by Prof. Brian Taylor, in Royal Entomological Society of London, England.